Functional aortic stiffness: role of CD4+ T lymphocytes - Majeed, Beenish A.; Eberson, Lance S.; Tawinwung, Supannikar; Larmonier, Nicolas; Secomb, Timothy W.; Larson, Douglas F. (Frontiers in Physiology, 2015)
The immune system is suggested to be essential in vascular remodeling and stiffening. To study the dependence upon lymphocytes in vascular stiffening, we compared an angiotensin II-model of vascular stiffening in normal C57BL/6J mice with lymphocyte-deficient RAG 1-/- mice and additionally characterized the component of vascular stiffness due to vasoconstriction versus vascular remodeling. Chronic angiotensin II increased aortic pulse wave velocity, effective wall stiffness, and effective Young’s modulus in C57BL/6J mice by 3-fold but caused no change in the RAG 1-/- mice. These functional measurements were supported by aortic morphometric analysis. Adoptive transfer of CD4+ T helper lymphocytes restored the angiotensin II-mediated aortic stiffening in the RAG 1-/- mice. In order to account for the hydraulic versus material effects of angiotensin II on pulse wave velocity, subcutaneous osmotic pumps were removed after 21 days of angiotensin II-infusion in the WT mice to achieve normotensive values. The pulse wave velocity decreased from 3- to 2-fold above baseline values up to 7 days following pump removal. This study supports the pivotal role of the CD4+ T-lymphocytes in angiotensin II-mediated vascular stiffening and that angiotensin II-mediated aortic stiffening is due to the additive effect of active vascular smooth muscle vasoconstriction and vascular remodeling.